Self-evaluation tool for culture of open scholarship services - Rantasaari Jukka; Ala-Mantila Minna; Hilska-Keinänen Katja; Jauhiainen Ilmari; Juppo Virpi; Kiviluoto Johanna; Koivula Hanna; Kärki Jussi; Laakso Kati; Lehtivuori Heli; Niemi Laura; Nokkala Tiina; et al. (Tieteellisten seurain valtuuskunta, 2025)
A self-evaluation tool for services has been developed to support the Policy for Open Scholarship, which takes into account the recommendations of all previous national policies on open science. The purpose of the tool is to assist research organisations in the self-evaluation and development of services and making them available. The organisation may produce the services alone, in cooperation with other organisations or utilise services at the national and international level. Measures promoting the openness of evaluation, learning, research data and publishing, which are also included in the Policy for Open Scholarship currently being prepared, are made concrete with minimum and ideal criteria. These criteria facilitate different target levels for different types of research organisations at different starting levels. The measures and criteria of the self-evaluation tool are also used in the national monitoring model for open science. The tool is intended for the self-assessment of organisations and the development of services, while the monitoring model makes it possible to assess the maturity level of the entire open science field.